Psychiatric disorders among medical students: how aware are we? - Ranjan, S; Shah, S; Aryal, S; Aich, TK (Journal of Universal College of Medical Sciences, 2014)
Studying medicine is a physically and emotionally demanding course. Several studies have documented that medical students are at high risk for developing psychiatric disorders. Also the risk increases because these students who are the future health care providers may misunderstand and stigmatize psychiatric disorders. This can be potentially tragic. This article reviews the data on prevalence of psychiatric disorders among medical students. PubMed and Medline were searched to identify latest peer-reviewed English-language studies reporting on depression, anxiety, suicide and other psychiatric disorders among medical students from different parts of the world. Searches were done using the key words medical students, psychiatric disorders, depression, burnout and suicide. References of the retrieved articles were inspected to identify relevant additional articles. The studies suggest a high prevalence of burnout, depression, suicide and other psychiatric disorders among medical students, higher than in the general population. Medical students are reluctant to seek psychiatric treatment more than the general population. The environment where they study may make them behave in the unprofessional way rather than the mental illness itself. Medical school is a time of significant psychological distress. Large, prospective, multicenter studies are needed to identify personal and training-related features that influence depression, anxiety, and burnout among students and explore relationships between distress and competency. DOI: http://dx.doi.org/10.3126/jucms.v1i4.9578 Journal of Universal College of Medical Sciences (2013) Vol.1 No.04: 56-60